2019
DOI: 10.1002/chem.201903969
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable and Inert Complexation of Indium(III) by Reinforced Cyclam Dipicolinate and a Bifunctional Derivative for Bead Encoding in Mass Cytometry

Abstract: H2cb‐te2pa, a cross‐bridged cyclam functionalized by two picolinate arms, was used for the formation of an incredible inert InIII chelate. The inertness of the complex was evaluated by UV/Vis experiments in several competitive media and was highlighted by the comparison with [In(dota)]− and [In(dtpa)]2− (H4dota = 1,4,7,10‐tetraazacyclododecane‐1,4,7,10‐tetraacetic acid, H5dtpa = diethylenetriamine pentaacetic acid), which are currently used in biological applications. For the first time, a bifunctional analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…These calculations showed that on average only 17 amine groups per chain were + was directly grafted onto polyamino beads. 19 In this + strongly suggests that the coupling of the complex on the polymer occurred. However, the signals of the biotin end-group cannot be clearly identified, which makes it difficult to calculate the number of grafted indium complexes by NMR.…”
Section: Preparation Of the Indium Polymermentioning
confidence: 85%
“…These calculations showed that on average only 17 amine groups per chain were + was directly grafted onto polyamino beads. 19 In this + strongly suggests that the coupling of the complex on the polymer occurred. However, the signals of the biotin end-group cannot be clearly identified, which makes it difficult to calculate the number of grafted indium complexes by NMR.…”
Section: Preparation Of the Indium Polymermentioning
confidence: 85%
“…+ was directly grafted onto polyamino beads. 19 In this work, the covalent attachment of the indium complex [In(p-NCS-CH 2 Ph-cb-te2pa)] + on the polylysine polymer PEG-poly(L-Lys)-Btn was also assured through the formation of very strong thiourea bonds (Figure 3). + strongly suggests that the coupling of the complex on the polymer occurred.…”
Section: Preparation Of the Indium Polymermentioning
confidence: 79%
“…All the ligands presented in this paper were synthesized as previously described in the literature. , Among them, the C- functionalized constrained cyclam derivatives have a structural interest because of the two potentially different relative positions of the ethylene cross-bridge and the C -appended hydroxyethyl pendant. During the synthesis, CB-cyclam-E and CB-DMC-E provided a mixture of syn and anti diastereoisomers as previously observed in our previous investigations . Crystals suitable for X-ray diffraction experiments, obtained from a solution containing a mixture of the two isomers, show evidence of the presence of both isomers (see Figure S3 and Table S1) in the crystal lattice.…”
Section: Results and Discussionmentioning
confidence: 95%